Tinjauan Pemusnahan Arsip Pada Kantor Korwil Bidang Pendidikan Dan Kebudayaan Kecamatan Leihitu - Kurnia Kapitanhitu; Vera Paulin Kay; Meiske H Tangnga (P3M Politeknik Negeri Ambon, 2023)
At the Korwil Office for Education and Culture in Leihitu District, the destruction of archives was not carried out according to the correct procedures. Archive destruction is carried out by burning, while the appropriate archive destruction procedure must go through the process of forming a committee, selecting archives, making a list of proposed archives for destruction, assessing archives, stages of requesting approval, stages of determining archives destroyed, and stages of implementing archive destruction accompanied by an official report. To find out how to implement effective archive destruction at the Regional Coordinating Office of the Leihitu District. This research is qualitative in nature where the author provides an overview of the destruction of archives at the Regional Coordinating Office of the Leihitu District. Data collection techniques used are observation, interviews, documentation and literature. Archive destruction at the Korwil Office is carried out by burning and only through the stages of requesting approval from the Head of Korwil and carrying out the destruction, this is not in accordance with ANRI Regulations where archive destruction should be carried out in 7 stages. The conclusion from this writing is that the destruction of archives at the Korwil office has not been carried out properly and does not follow clear guidelines/references, the destruction of archives should be carried out according to procedures consisting of 7 stages namely forming a committee, selecting archives, making a list of proposed archives for destruction, evaluating archives, application for approval, and finally the implementation of archive destruction. The implementation of archive destruction at the Korwil office has not been carried out properly and does not follow clear guidelines/references. The importance of conducting Archiving socialization/training to archive managers, this aims to increase awareness of the importance of managing records properly.